Mendorong Pertumbuhan Industri Halal: Identifikasi Faktor Strategis Melalui Analisis SWOT - Tampubolon, Arsyaf; Nawawi, Zuhrinal; Ramadhan, Muhammad (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study aims to identify the strategic factors influencing the growth of the halal industry through a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Using a qualitative literature review approach, relevant research articles published between 2021 and 2025 were analyzed. The findings indicate that the halal industry's main strengths lie in strong government support, its contribution to the Sustainable Development Goals (SDGs), a universal market base, and the Halal-Tayyiban concept. However, significant weaknesses persist, including the lack of harmonized global standards, limited infrastructure, and technological gaps. Opportunities are identified in digital transformation, the growing young Muslim population, and expansion into non-traditional markets, while threats include intense global competition and political-economic instability. Based on the analysis, strategic recommendations are proposed, focusing on the harmonization of global halal standards, investment in infrastructure and technology, human resource capacity building, enhanced branding, and the development of a collaborative ecosystem. These measures are expected to accelerate the growth of a sustainable and globally competitive halal industry.